590Online + In-person: A Model for the Instruction of Contemporary Epidemiologic Methods in Resource-Limited Settings. (2nd September 2021) - Avelino-silva, Vivian; Semeere, Aggrey; Laker-Oketta, Miriam; Byakwaga, Helen; Pletcher, Mark; Martin, Jeffrey
Abstract: Focus of Presentation: Many low-income countries cannot support faculty to develop contemporary graduate-level courses in epidemiology and biostatistics. There are also insufficient resources to support all students who are interested in traveling abroad to study in resource-rich settings. To address this, we describe our experience with training a few students from resource-limited countries in the U.S. who have subsequently returned to their home countries and became instructors in a novel online plus in-person teaching model. Findings: Most courses at our major U.S. training program in epidemiology videotape lectures for viewing on one's own and post all other materials (e.g., homework) on the course's website. The weekly learning cycle culminates with an in-person high-level small group discussion, led by a faculty member who facilitates 10-15 students. For the past 5 years, non-U.S. scholars from Africa and South America who have taken our courses in the U.S. have travelled back to their countries and become small group leaders for our courses. Identical to U.S. students, the students in these international venues view videotaped lectures, access other materials online, and have weekly in-person small group discussions. These international students represent another concurrent small group for the U.S-based course; they have identical access and evaluation. Conclusions: By pairing online resources from a resource-rich setting with local in-person instruction, we provide students in resource-limited settings access to contemporary instruction in epidemiology at very low cost. Key messages: Online plus local in-person teaching is a feasible model for providing instruction regarding epidemiologic methods in resource-limited settings.